Safety of Laparoscopy in Patients with Ventriculoperitoneal Shunts - Sarah A. Mohamed (Emergency Department of Hospital San Pedro (Logroño, Spain), 2021)
The relationship between the intra-abdominal pressure (IAP) and intracranial pressure (ICP) has been suspected for more than 100 years and was subsequently confirmed by numerous studies in both animals and humans which demonstrate the link and the positive correlation between IAP and ICP. There are mounting concerns that the pneumoperitoneum created during laparoscopic surgery to create space for instrument placement and to allow safe tissue dissection may result in an increase in the ICP secondary to the increase in the IAP which may result in serious consequences in patients with Ventriculoperitoneal (VP) shunts. There is uncertainty about the safety of laparoscopic surgery in VP shunt patients. The aim of this article is to review the literature to answer the question [Is laparoscopic surgery safe in VP shunt patients with and without intraoperative monitoring of ICP]?